Design of a Teflon‐Like Anion for Unprecedently Enhanced Lithium Metal Polymer Batteries. Issue 15 (25th February 2023) - Tong, Bo; Song, Ziyu; Feng, Wenfang; Zhu, Jing; Yu, Hailong; Huang, Xuejie; Armand, Michel; Zhou, Zhibin; Zhang, Heng
Abstract: Rechargeable lithium metal polymer batteries (LMPBs) utilizing solid polymer electrolytes (SPEs) have gained increasing attention during the past five decades, owing to the superior flexibility, good process‐ability, and no‐leakage of SPEs versus traditional non‐aqueous liquid and inorganic solid electrolytes. Undoubtedly, among all of the SPE components, salt anions have a significant impact on the overall performances of LMPBs. Yet, lithium bis(trifluoromethanesulfonyl)imide, being commonly applied in the prevailing SPEs shows relatively poor interphasial stability toward lithium metal (Li°) anode, which greatly impedes the long‐term cycling stability of LMPBs. Herein, a Teflon‐like sulfonimide salt, lithium bis( n ‐nonafluorobutanesulfonyl)imide (LiNFSI), is ingeniously selected for modulating the properties of solid–electrolyte‐interphases on the anode side, in view of the peculiar film‐forming ability of n ‐nonafluorobutanesulfonyl group. In‐depth physical, chemical, and electrochemical characterizations demonstrate that the incorporation of the Teflon‐like anion, NFSI −, results in a remarkably enhanced electrochemical stability between Li° anode and SPEs, with a negligible expense of ionic conductivities. The Teflon‐like sulfonimide anion suggested in this work provides an elegant path toward the wider application of LMPBs in energy storage and electric vehicles in the near future. Abstract : The Teflon‐like anion, bis( n ‐nonafluorobutanesulfonyl)imide, is capable of forming fluorinated oligomers/polymers and lithium fluoride under reductive decompositions, which significantly enhances the elasticity and mechanical stability of the as‐formed solid–electrolyte‐interphase layer on lithium metal anode, thus improving the cycling performance of rechargeable lithium metal polymer batteries.